Eksplorasi Etnomatematika pada Benteng None di Desa Tetaf Kabupaten Timor Tengah Selatan dan Integrasinya dalam Pembelajaran Matematika - Jesika Yannaci Teftae; Dominikus Wara Sabon; Aleksius Madu (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
Students often perceive mathematical concepts as abstract due to a lack of relevant context. This research is based on the assumption that ethnomathematics, as the study of the relationship between culture and mathematics, can be used to bridge this gap, making learning more meaningful through the utilization of local cultural practices. Benteng None was chosen as the object of exploration due to its rich history and cultural elements, which are thought to contain mathematical concepts. This research aims to describe the history and philosophy of Benteng None; explore the ethnomathematics found in Benteng None; identify the school mathematics concepts contained within these ethnomathematic elements; and describe the results of integrating Benteng None ethnomathematics into mathematics learning. This research used a descriptive qualitative method with an ethnographic approach. The research location was Benteng None, Tetaf Village. Data collection was conducted through triangulation of observation, interviews, and documentation techniques, with research subjects including traditional leaders and the local community. Data were analyzed to identify mathematical activities and concepts, which were then integrated into learning materials. The results show that Benteng None contains various ethnomathematics elements related to locating, measuring, designing, counting, explaining, and playing. The school mathematics concepts successfully identified and linked in Benteng None include plane figures, angles and vectors, measurement, derivatives, circles, cylinders and cones, and time and duration. These school mathematics concepts within the Benteng None culture can be developed through the design of learning tools that are aligned with school mathematics.